Iatrogenic pulmonary artery rupture during Swan–Ganz catheter placement—A novel therapeutic approach1. Issue 1 (21st May 2012) - Kalra, Ankur; Heitner, Stephen; Topalian, Simon
Abstract Pulmonary artery rupture (PAR) is a rare but deadly complication (incidence of 0.03–0.2% of all PA cannulations), with mortality in the region of 70%. We report a case of an 88‐year‐old woman with iatrogenic PAR as a result of Swan–Ganz catheter placement. A rapid successful isolation and occlusion of the culprit PA branch via the deployment of an Amplatzer® Vascular Plug (AGA Medical Corporation, North Plymouth, MN) was performed. To our knowledge, this is the first case report where this device has been used as therapy in PAR. © 2012 Wiley Periodicals, Inc.